Si Tole Game to Improve Students' Critical Thinking Skills on Reaction Rate Material - Purnomo, Syafa Aisyah Ayu; Rusmini, Rusmini (Electronic Journal of Education, Social Economics and Technology, 2025)
The learning media used by most teachers in schools are power point and whiteboard media. However, these media do not significantly influence students' learning motivation, leading to a decrease in their critical thinking skills. In contrast, the independent curriculum requires students to fulfill the learning objectives for critical thinking. Dengan tujuan untuk meningkatkan kemampuan berpikir kritis siswa pada materi laju reaksi, penelitian ini mencoba membuat media permainan Si Tole. This study uses a research and development model according to Borg and Gall. The data obtained were then analyzed for validity, practicality, and effectiveness. The validity analysis findings demonstrated that the Si Tole game medium met excellent standards for validity, 93% of the findings of the practicality analysis met the practical requirements and the effectiveness analysis's findings yielded a gain value of 0.8 with a high category. So, it can be concluded that the Si Tole game media is valid, practical, and effective in improving students' critical thinking skills in the reaction rate material.